Fenomena Pengalihan Sunrang Kepada Anak di Kabupaten Gowa: Analisis Kaidah Al-‘Aadatu Muhakkamah - Mappaseleng, Mappaseleng; Widjaja, Abdi; Anis, Muhammad; AR, Amril Maryolo (Universitas Islam Negeri Alauddin Makassar, 2024)
A polemic that often occurs in the community, especially in Gowa Regency, is the diversion of sunrang to children which often causes problems. So there are often problems in the family that cause disputes between the first child and his other siblings. The main problem in this study is how to transfer sunrang to children in Sapaya village, Bungaya district, Gowa regency, How to analyze the rule of al-'Aadatul Muhakkamah on the phenomenon of transferring sunrang to children in Sapaya Village, Bungaya District, Gowa Regency. This type of research is field research. The approaches used are the Normative Syar'i Approach and the Sociological approach. The methods used in this study are observation, interviews and documentation. From the results of research conducted by researchers on the phenomenon of the transfer of sunrang to children in Sapaya Village, Bungaya District, it shows that the transfer of sunrang to children is carried out in a hereditary manner which is passed on by the community in Sapaya Village. However, the existence of this diversion causes injustice in the provision of sunrang because only the first child is prioritized while the other children do not have the right to receive the transfer of sunrang. The implications of this study are expected to reduce disputes in the diversion of sunrang.